(untitled) (Research, Society and Development, 2021)
The objective was to highlight the direct relationship between the number of cases of violence and the SARS-CoV-2 pandemic. This is an integrative literature review, of a descriptive type, through the search via the Virtual Health Library, selecting the databases: Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Literature in Health Sciences and the Nursing Database - Brazilian Bibliography, through the use of Health Sciences Descriptors: COVID-19, Violence and Pandemic, added to the Boolean operator AND, between the years 2018 to 2020, thus selecting 09 articles for the preparation of the study. The cases of violence against women and children occur frequently and for a long time, mainly due to the influence of the patriarchy that is established in society, the pandemic and social isolation came as an aggravating factor in the face of this situation. It is concluded that in many studies the number of cases of violence was lower than in previous years, but that this may have a direct relation to how much health services and actions were affected during the pandemic of the new coronavirus.